Humayma's notched peak: a focus of Nabataean and Roman veneration and civic identity. (November 2016) - Reeves, M. Barbara
Abstract : The most distinctive landscape feature at the southern Jordanian site of Humayma is Jebel Qalkha's highest peak, which is split at the top by a wide notch. The Nabataean town of Hawara (Roman Hauarra/Hauara) was built on the plain immediately east of this peak. This paper draws on the site's foundation myth, petroglyphs, betyls and religious and civic structures to illustrate the significance of this notched peak for the site's ancient populations. The evidence suggests that this distinctive peak served as a focus of veneration and a marker of civic identity for Humayma's Nabataean and Roman inhabitants.